A Car Logo Design-Inspired CPW-Fed Semitransparent Antenna for Vehicular Applications - Lekha Kannappan; Sandeep Kumar Palaniswamy; Malathi Kanagasabai; Sachin Kumar (International Journal of Antennas and Propagation)
In this paper, a quad-port multiple-input multiple-output (MIMO) semitransparent antenna is designed for automotive applications. The transparent soda lime glass substrate is used in the prototype antenna for windshield applications, and the radiator is nontransparent copper metal. The unit cell radiator of the MIMO antenna is similar to the “NISSAN automobile-like” logo. The proposed MIMO antenna has a −10 dB impedance bandwidth of 3.4 to 11 GHz. The edge-to-edge distance between the elements in the MIMO configuration is 6 mm. The antenna elements are perpendicularly oriented to offer dual (horizontal and vertical) polarization, which aids in providing better isolation and good signal reception in all directions. The isolation between the resonating elements is greater than 15 dB without the use of any decoupling structure. The diversity metrics are examined in order to gain a better understanding of the MIMO antenna performance. The envelope correlation coefficient (ECC) is less than 0.01, diversity gain (DG) is greater than 9.98 dB, and the total active reflection coefficient (TARC) and channel capacity loss (CCL) are less than −10 dB and 0.07 bits/s/Hz, respectively. The quad-port MIMO antenna offers transparency of 52.26% over the entire area. The proposed antenna could be suitable for automotive applications such as intelligent transportation systems (ITS), vehicular communications, and the automatic vehicle identifier (AVI).